Integrating industrial maintenance strategy into ERP - Nikolopoulos, K; Metaxiotis, K; Lekatis, N; Assimakopoulos, V (Industrial management + data systems, 2003)
During the last decade, many companies have made large investments in the development and implementation of enterprise resource planning (ERP) systems. However, only few of these systems developed or installed have actually considered maintenance strategies. Maintenance is a complex process that is triggered by planned periodic repair (scheduled or planned maintenance), equipment breakdown or deterioration indicated by a monitored parameter (unplanned or emergency maintenance). This process requires planning, scheduling, monitoring, quality assurance and deployment of necessary resources (workshop, manpower, machines, equipment, tools, spare parts, materials). Proper design and integration of maintenance management into ERP systems enable enterprises to effectively manage their production planning and scheduling, as well as to analyze their maintenance history so as to carry out cost analysis and produce future projections of failure trends. The present work presents the design of an object-oriented maintenance management model and its integration into an ERP system. The proposed model was designed towards the development of innovative industrial software regarding the optimum management of maintenance in a wide range of business areas.